Accountability and Transparency Of Financial Reporting Village Owned Business Entities - Tri Hartanto, Dimas Wegig; Labib Muttaqin (Jurnal Hukum dan Kenotariatan, 2024)
This research aims to determine the concepts and regulations regarding the accountable and transparent BUMDes financial reporting process and its implementation at BUMDes Sumber Rejeki Jati Batur. This research is empirical legal research. Data collection was carried out through observations and interviews in the field as well as collecting relevant literature. Data analysis techniques and data presentation by collecting field information are then connected to theories and regulations obtained from literature studies. Based on the research conducted, 2 (two) conclusions were found, namely: (a) The concept of regulating BUMDes financial reports that is accountable and transparent includes semi-annual and annual periodic reports. Furthermore, the annual report is submitted in the village deliberation forum/inter-village deliberation. Ultimately, the report is published to the wider public to ensure the principles of accountability and transparency; and (b) Administratively BUMDes Sumber Rejeki Jati Batur has implemented the principles of accountability and transparency as mandated by existing regulations. However, technically it cannot be exactly the same as the applicable regulatory mandate.